Combination Interactive Effects of Gongronema latifolium Leaves and Picralima nitida Seeds Extracts on Glucose Tolerance - Egbuniwe, Maureen Ifeyinwa; Ozoani, Harrison Anezichukwu; Ajaghaku, Amara Anwuchaepe; Mbagwu, Ikechukwu Sonne; Orji, Uchechukwu Harrison; Ajaghaku, Daniel Lotanna (Biology, Medicine, & Natural Product Chemistry, 2023)
This study evaluated the combination interactive effects of G. latifolium leaves and P. nitida seed extracts using a metabolic glucose tolerance test. The plant samples were extracted separately using cold maceration and their acute toxicities were determined. Dose-response glucose tolerant tests of both plants were done using a 2 g/kg glucose load monitored over 0 – 1h. A 41% effect isobologram was used to determine the needed dose combinations according to the principle of Loewe’s additivity model. The glucose tolerant tests of dose pairs of the combined extracts were evaluated and their combination indices were calculated to determine the nature of their interaction. The ED41 of G. latifolium (GL) and P. nitida (PN) were 180 mg/kg and 254 mg/kg respectively. The percentage reductions of GL:PN (50:160); GL:PN (100:90); and GL:PN (150:30) dose pairs were 48.23, 50.76 and 42.99 % respectively. Their combination index were calculated to be 0.91, 0.91 and 0.95 respectively - an indication of synergistic interaction. Findings from this study validate the combined use of G. latifolium leaves and P. nitida seeds in folkloric medicine. However, combining the extracts of G. latifolium: P. nitida in the dose ratios of 50:160, 100:90 and 150:30 mg/kg gave the best dose pairs with synergistic outcome.